Use of standardized outcome measures among physical therapists in the United States: A cross-sectional survey study - Anat Kristal; Ignacio A. Gaunaurd; Sara J. Morgan; Geoffrey S. Balkman; Rachael E. Rosen; Rana Salem; Alyssa M. Bamer; Brian J. Hafner (PLoS ONE, 2025)
As value-based care becomes increasingly central to healthcare delivery in the United States, physical therapists (PTs) are expected to use outcome measures (OMs) to demonstrate meaningful improvements in patient health. Although OMs play a critical role in supporting value-based practice, prior research suggests they are not routinely used, and limited attention has been given to how resource availability may influence their implementation, particularly for performance-based tests. This study aimed to assess PTs’ use of OMs, including their perceptions of value, motivations for use, and the resources available for administration. An online survey was used to evaluate outcomes measurement practices of PTs in the United States. Invitations were mailed to a random sample of American Physical Therapy Association members. Frequencies and percentages were calculated. Nearly all respondents (n = 514) used OMs with their patients, but performance-based tests were used more than self-report surveys (97% and 83%, respectively). Most respondents agreed that OMs were within their scope of practice (>95%) and could be administered with knowledge they possessed (>88%). However, less than 50% agreed OMs are administered in a standardized manner across the profession. Most respondents (89%) indicated that performance-based tests “help me make clinical decisions,” but fewer (61%) said the same about self-report surveys. Respondents were also willing to dedicate more time to performance-based tests than self-report surveys (up to 20 and 10 minutes, respectively). Most respondents (>80%) indicated they had smaller rooms and short hallways (≤10m) for OM administration. Results of this study indicate PTs in the United States have the knowledge, time, and space to administer many of the OMs recommended for use in physical therapy. While PTs use both types of OMs, performance-based tests are often perceived to have greater clinical value. Obtaining consensus on specific protocols for administering OMs may help to address concerns about the lack of standardization across the profession.